A novel 3D variational aeroelastic framework for flexible multibody dynamics: Application to bat-like flapping dynamics. (15th February 2019) - Li, G.; Law, Y.Z.; Jaiman, R.K.
Highlights: New variational aeroelastic framework for 3D turbulent flow and flexible multibody interaction. Coupling of the RBF-based aeroelastic coupling method with NIFC scheme. Integration of multibody aeroelastic solver with DDES model for high Reynolds number. Validation of coupled aeroelastic framework for a realistic flexible flapping wing. Application of aeroelastic framework for bat-like wing in gliding and flapping flight conditions. Abstract: We present a novel three-dimensional (3D) variational aeroelastic framework for flapping wing with a flexible multibody system subjected to an external incompressible turbulent flow. The proposed aeroelastic framework consists of a three-dimensional fluid solver with a hybrid RANS/LES model based on the delayed detached eddy simulation (DDES) treatment and a nonlinear monolithic elastic structural solver for the flexible multibody system with constraints. Radial basis function (RBF) is applied in this framework to transfer the aerodynamic forces and structural displacements across the discrete non-matching interface meshes while satisfying global energy conservation. For the consistency of the interface data transfer process, the mesh motion of the fluid domain with large elastic deformation due to high-amplitude flapping motion is also performed via the standard radial basis functions. The fluid equations are discretized using a stabilized Petrov–Galerkin method in space and the generalized- α approach is employed to integrate the solution in time. The flexible multibody system is solved by using geometrically exact co-rotational finite element method and an energy decaying scheme is used to achieve numerical stability of the multibody solver with constraints. A nonlinear iterative force correction (NIFC) scheme is applied in a staggered partitioned iterative manner to maintain the numerical stability of aeroelastic coupling with strong added mass effect. An isotropic aluminum wing with flapping motion is simulated via the proposed aeroelastic framework and the accuracy of the coupled solution is validated with the available experimental data. We next study the robustness and reliability of the 3D flexible multibody aeroelastic framework for an anisotropic flapping wing flight involving battens and membranes with composite material and compare against the experimental results. Finally, we demonstrate the aeroelastic framework for a bat-like wing and examine the effects of flexibility on the flapping wing dynamics.